2017
DOI: 10.7863/ultra.16.08033
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse Quantification in the Evaluation of Renal Parenchyma Elasticity in Pediatric Patients With Chronic Kidney Disease: Preliminary Results

Abstract: Acoustic radiation force impulse may be a potentially useful tool in detecting CKD in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…In addition to SWE evaluations of healthy kidneys, considerable numbers of SWE studies have been conducted to assess various diseases of the kidneys. Bilgici et al found decreased SWV values in kidneys with chronic renal failure compared to normal ones in a pediatric population. Takata et al found decreased SWV values in chronic renal failure using acoustic radiation force impulse imaging; however, in their study, no significant difference was observed between the kidneys with the early‐stage renal parenchymal disease and the kidneys with end‐stage renal disease.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to SWE evaluations of healthy kidneys, considerable numbers of SWE studies have been conducted to assess various diseases of the kidneys. Bilgici et al found decreased SWV values in kidneys with chronic renal failure compared to normal ones in a pediatric population. Takata et al found decreased SWV values in chronic renal failure using acoustic radiation force impulse imaging; however, in their study, no significant difference was observed between the kidneys with the early‐stage renal parenchymal disease and the kidneys with end‐stage renal disease.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the above-mentioned studies, Bob et al [ 15 ] reported that the ARFI-e measurement values of the patient group were lower than those of the control group in a study of adult patients diagnosed with GN. Similarly, the renal parenchyma was evaluated with ARFI-e in pediatric patients with CKD by Bilgici et al [ 27 ]. The mean SWV values of the patient group were lower than those of the control group [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the renal parenchyma was evaluated with ARFI-e in pediatric patients with CKD by Bilgici et al [ 27 ]. The mean SWV values of the patient group were lower than those of the control group [ 27 ]. These studies differed from the present study in terms of the included patient population and type or stage of kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results about the alterations of SWV values for damaged renal parenchyma in literature. Bilgici et al [31] and Hu et al [32] reported that SWV values decrease with chronic renal failure compared to healthy paediatric kidneys. Takata et al [33] found decreased SWV values in chronic renal failure; however, in their study, no significant difference was observed between the kidneys with early-stage renal parenchymal disease and the kidneys with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%